(untitled) (Journal of Hama University, 2020)
The sides effects of dental caries preparation and restoration on pulp vitality vary significantly, and could exacerbate in deep restorations, leading to serious functional disorder then necrosis of pulp at the long term. The aim of this study is to investigate the effect of monomers penetration of deep composite restoration, via dentinal tubuli, on the rate & nature of cellular division in dental pulp. Human teeth, scheduled for orthodontic extraction, have been used, where divided into (9) groups to follow the effects of etching technique, and light-curing period of deep composite restorations on cellular division in dental pulp, using immunohistochemical marking via monoclonal antibodies Ki-67 and p53. Marking carried out after 3 weeks and 3 months from restoration, modifications in Ki-67 and p53 expression levels were followed, and function of gradual quantitative criteria regarding spreading and concentration index of pulpal stained cells. Statistical Analysis (P<0.05) show significant differences between some studied groups. The minimal pulp disorders are detected using Self-etching, with long light-curing period, showing reduced expression level of Ki-67 and p53. The maximal pulp disorders are detected using total etch, with short light-curing period, showing simultaneous increasing level of Ki-67 and p53 expression, indicating a potential injury in DNA chains of mitotic cells. We conclude that the dentinal infiltrated monomers could cause oxidative stress and early pulp fatigue in deep composite restorations, so it is recommended to use self-etching, maintaining moderate dentinal permeability, and long light-curing period, in order to improve the polymerization conversion rate.